Revision of Phaenocora Ehrenberg, 1836 (Rhabditophora, Typhloplanidae, Phaenocorinae) with the description of two new species - Houben, A. M.; Van Steenkiste, N.; Artois, T. J. (Zootaxa, 2014)
A morphological and taxonomical account of the taxon Phaenocora is provided. An effort was made to locate and study all available material and, where possible, species are briefly re-described. We also describe two new species: Phaenocora gilberti sp. nov. from Cootes Paradise, Ontario, Canada and Phaenocora aglobulata sp. nov. from Prairie Grove, Alabama, USA. Species recognition is based on a combination of both male and female morphology. A comparison of and discussion on all species is given, resulting in a total of 28 valid species, three species inquirendae, five species dubiae, and one nomen nudum. An identification key is provided.